EFEKTIVITAS PENGGUNAAN ASET DAERAH PADA BADAN KEUANGAN DAN ASET DAERAH KABUPATEN PANIAI - Yance Nawipa; Sadly Abdul Djabar; Mujahid Mujahid (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to examine how regional assets are used at the Paniai Regency Regional Finance and Asset Agency. The research method used was a descriptive qualitative approach, with data analysis through interviews and field observations. Key informants were obtained through interviews with five individuals. The results indicated that the asset utilization system is ineffective. Asset management still lacks an integrated application, human resources are low, they have never participated in training, workshops, or workshops on asset management, the planning system is suboptimal, assets are controlled by certain individuals in large numbers, and some assets are used by individuals outside the scope of the Regional Work Unit (SKPD). Internal factors include the suboptimal competence of managing officials, who have never participated in technical guidance, training, or training on asset management. External factors include the lack of a specific budget allocation for human resource development for asset management, as well as social, cultural, and geographic conditions, as well as public awareness of participation and understanding the importance of properly protecting, maintaining, and managing assets.